Effect of salt stress on the photosynthetic characteristics and endogenous hormones, and: A comprehensive evaluation of salt tolerance in Reaumuria soongorica seedlings. (31st December 2022) - Yan, Shipeng; Chong, Peifang; Zhao, Ming
ABSTRACT: Salinity is a major limiting factor in desert ecosystems, where Reaumuria soongarica is a dominant species. It is crucial to study the growth and physiological response mechanisms of R. soongorica under salt stress for the protection and restoration of the desert ecosystems. However, the effects of salt concentration and stress duration on endogenous hormonal content and photosynthetic efficiency and salt injury index of R. soongorica leaves have not been reported. Currently, there is no systematic evaluation system to determine physiological adaptation strategies of R. soongorica seedlings in response to salt stress. In this study, simulation experiments were performed with NaCl solution mixed with soil. Enzyme-linked immunosorbent assay and LI-6800 portable photosynthesis analyzer were used to measure indole acetic acid (IAA), corn nucleoside hormone (ZR), abscisic acid (ABA), and photosynthesis-related parameters in leaves of R. soongorica seedlings at 0 (24–48 h after salt treatment), 3, 6, and 9 days. At the same time, growth indicators (salt injury index, root-to-shoot ratio), reactive oxygen species content, superoxide dismutase enzyme (SOD) activity, osmolyte content, membrane peroxidation, and leaf pigment content were measured at different salt concentrations and treatment times. Finally, principal component analysis and membership function method were used to comprehensively evaluate the salt tolerance of seedlings. The results showed that treatment with 200 mM NaCl for 3 days significantly increased SOD activity, the content of osmotic adjustment substances (proline, soluble protein), endogenous hormone content (ABA, ZR), root-to-shoot ratio, and Chla/Chlb values but decreased malondialdehyde content (MDA) in the leaves of R. soongorica seedlings. Leaf water content (LRWC), net photosynthetic rate (Pn), transpiration rate (Tr), water use efficiency (WUE), and IAA content in R. soongorica seedlings were lower than those in the control, when exposed to 400 and 500 mM NaCl solutions. Finally, the principal component analysis revealed endogenous hormone content and antioxidant enzyme activity to be useful for the comprehensive evaluation of salt tolerance in R. soongorica seedlings. The R. soongorica seedlings showed the strongest salt tolerance when exposed to 200 mM NaCl for 3 days. This study provides a theoretical foundation for gene mining and breeding of salt-tolerant species in the future.